A comparative analysis of gene and protein expression in chronic and acute models of photoreceptor degeneration in adult zebrafish - Kramer, Ashley C.; Carthage, Justin; Berry, Yasmeen; Gurdziel, Katherine; Cook, Tiffany A.; Thummel, Ryan (Frontiers in Cell and Developmental Biology, 2023)
Adult zebrafish are capable of photoreceptor (PR) regeneration following acute phototoxic lesion (AL). We developed a chronic low light (CLL) exposure model that more accurately reflects chronic PR degeneration observed in many human retinal diseases. Here, we characterize the morphological and transcriptomic changes associated with acute and chronic models of PR degeneration at 8 timepoints over a 28-day window using immunohistochemistry and 3'mRNA-seq. We first observed a differential sensitivity of rod and cone PRs to CLL. Next, we found no evidence for Müller glia (MG) gliosis or regenerative cell-cycle re-entry in the CLL model, which is in contrast to the robust gliosis and proliferative response from resident MG in the AL model. Differential responses of microglia between the models was also observed. Transcriptomic comparisons between the models revealed gene-specific networks of PR regeneration and degeneration, including genes that are activated under conditions of chronic PR stress. Finally, we showed that CLL is at least partially reversible, allowing for rod and cone outer segment outgrowth and replacement of rod cell nuclei via an apparent upregulation of the existing rod neurogenesis mechanism. Collectively, these data provide a direct comparison of the morphological and transcriptomic PR degeneration and regeneration models in zebrafish.